Urgensi Penguatan Kompetensi Pedagogik Guru Berbasis Multiple Intelegensi Pada Sekolah Dasar - Ayi Abdurahman; Hermin Nainggolan; Nurul Hikmah; Via Yustitia; Yanry Budianingsih (Journal on Education, 2023)
The purpose of this study was to determine the process of developing teaching e-modules, the feasibility of teaching e-modules and this research has the goal of understanding the Urgency of Strengthening Teacher Pedagogic Competence Based on Multiple Intelligences (Intellectual, Emotional and Spiritual) in Elementary Schools. The study method used is literature study with a content analysis approach. The results of this paper as a whole found that strengthening teacher pedagogic competence is an important target that continues to be developed by schools and stakeholders because the teacher's role is crucial in determining the level and quality of learning that will affect the improvement of the quality of national education, especially in basic education. Related to the urgency of strengthening teacher pedagogic competence based on Multiple Intelligences where, One of the most challenging consequences in the theory of multiple intelligences is if educational institutions, including Elementary Schools, have the effort and responsibility to pay attention to the talents of each student in the learning process. At the elementary school level, the theory of multiple intelligences can be implemented in all subjects. Therefore the multiple intelligence model encourages educators to present units or learning in ways that involve students' feelings more